2017
DOI: 10.1186/s12960-017-0241-0
|View full text |Cite
|
Sign up to set email alerts
|

Professional fulfillment and parenting work-life balance in female physicians in Basic Sciences and medical research: a nationwide cross-sectional survey of all 80 medical schools in Japan

Abstract: BackgroundIn Japan, the field of Basic Sciences encompasses clinical, academic, and translational research, as well as the teaching of medical sciences, with both an MD and PhD typically required. In this study, it was hypothesized that the characteristics of a Basic Sciences career path could offer the professional advancement and personal fulfillment that many female medical doctors would find advantageous. Moreover, encouraging interest in Basic Sciences could help stem shortages that Japan is experiencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 24 publications
3
16
0
Order By: Relevance
“…Fifteen of the 18 students who went on to start their research career in the basic sciences expressed a strong curiosity for finding out something new that had never been known or discovered before (McGee and Keller 2007). The results of the present study also support the findings in our previous studies in Japan in which medical students mentioned that attempting unknown things was a major point of the basic sciences (Yamazaki et al 2013) and research interest was the primary motivation to choose a career in basic sciences for female physicians (Yamazaki et al 2017). …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Fifteen of the 18 students who went on to start their research career in the basic sciences expressed a strong curiosity for finding out something new that had never been known or discovered before (McGee and Keller 2007). The results of the present study also support the findings in our previous studies in Japan in which medical students mentioned that attempting unknown things was a major point of the basic sciences (Yamazaki et al 2013) and research interest was the primary motivation to choose a career in basic sciences for female physicians (Yamazaki et al 2017). …”
Section: Discussionsupporting
confidence: 87%
“…Therefore, in 2012, we conducted a questionnaire survey focusing on all female physicians employed as an assistant professor or higher in basic science departments at all 80 medical schools in Japan to investigate which aspects of their work led to professional advancement and personal fulfilment. The quantitative results have already been published and have revealed that although female basic science physicians with children tend to express second thoughts about relinquishing a full-time clinical practice, they generally benefited from better work flexibility, with no significant effect on career development and salary as basic scientists (Yamazaki et al 2017). Among the questions asked, one qualitative question asked respondents to write down their thoughts on what positive aspects of their work in basic sciences were different from working in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…Although the MD-PhD program has recently been introduced in Japan’s medical education program, there are very few students who have applied to this program [ 25 ]. More efforts to arouse interest in science in young medical students are definitely required [ 26 ]. In the same model, an increase in research budget was also associated with the negotiation for a reduction of clinical duty hours and an opportunity for promotion, which suggests that the higher the grant amount the physician scientist receives, the more pressure they may perceive.…”
Section: Discussionmentioning
confidence: 99%
“…The role of nurse practitioners in Canada was originally intended to meet the medical/healthcare needs of underserved populations residing in remote rural areas in northern parts of the country [16]. According to this concept [16], nurse practitioners in rural communities of Japan can assist with medical care on behalf of physicians, thereby helping physicians enhance their work and lifestyle [17,18]. At present, nurse practitioners have been serving in many roles in a variety of medical/healthcare settings, such as prescribing practices [19], chemotherapy [20], and memory assessment services for people with suspected dementia [21].…”
Section: Discussionmentioning
confidence: 99%